Does a work-stress intervention prevent sick leave? A randomized controlled trial in primary care. (30th September 2020) - Hultqvist, J; Bjerkeli, P; Hensing, G; Holmgren, K
Abstract: Background: Work-related stress (WRS) clearly presents a risk for sick-leave. A brief preventive intervention aiming to identify people at risk for WRS was tested in a RCT study in primary health-care centers (PHCC). At the 12-month follow-up there were differences regarding sick leave between the intervention and the control group, however they did not become statistically significant. Evaluating the intervention in a longer perspective is thus warranted. Purpose: This study aims to evaluate whether a systematic early identification of work-related stress can prevent sickness absence over 18 to 24 months after the intervention. Methods: The RCT-study had follow-ups at 18 and 24 months. The participants (N = 271) were employed, non-sick-listed women and men (18 to 64 years) seeking care at PHCCs for mental and physical health complaints. 132 patients were allocated to the intervention and 139 patients were allocated to treatment as usual. The preventive intervention included early identification of WRS by the Work Stress Questionnaire (WSQ), general practitioner (GP) awareness supported by a brief training session, patients' self-reflection by WSQ completion, GP giving the patient feedback at consultation, and identifying appropriate preventive measures. Sick leave data from the Swedish Social Insurance Agency register constituted the outcome comparing the preventive intervention by the GP versus treatment as usual. Results: The preliminary results showed that there were differences in median sick days between the intervention group (68, 72) and the control group (80, 81) at 18 months and at 24 months, however these differences did not become statistically significant. Conclusions: The WSQ brief intervention was not proven effective in preventing sick leave in the following 18 and 24 months compared to treatment as usual. The study may have been under-powered and the lack of statistical difference between the groups might be due to a type II error. Key messages: Work-related stress is a predictor for sick-leave. Further research on how to identify those at high risk for sick-leave, give advice and treat this group in primary health care is needed. A study of the WSQ brief intervention with a larger sample seems warranted.